Getting lost in a story: how narrative engagement emerges from narrative perspective and individual differences in alexithymia. Issue 3 (3rd April 2021) - Samur, Dalya; Tops, Mattie; Slapšinskaitė, Ringailė; Koole, Sander L.
ABSTRACT: The present research examines how narrative engagement, or the extent to which people immerse themselves into the world of a story, varies as a function of narrative perspective and individual differences in alexithymia. The authors hypothesised that narrative engagement would be higher when people assume a first-person (rather than third-person) perspective and for people lower (rather than higher) on alexithymia. In an online study ( N = 541) and a lab study ( N = 55), participants with varying levels of alexithymia read first- and/or third-person narrated texts and then rated their narrative engagement. As expected, first-person stories evoked more narrative engagement than third-person stories, and global alexithymia was negatively correlated with narrative engagement. Narrative perspective did not interact with cognitive facets of alexithymia (i.e. difficulties identifying, verbalising, and understanding feelings). However, narrative perspective did interact with affective facets of alexithymia (i.e. emotionalising and fantasising): First-person (rather than third-person) stories elicited more narrative engagement at lower levels of affective alexithymia, but not at higher levels of affective alexithymia. The interaction effect was significant in Study 1; the interaction was significant in Study 2 after controlling for trait absorption. Together, these findings suggest that alexithymia is linked to difficulties in mentally simulating narrative worlds.